2017
DOI: 10.1021/acsnano.7b02857
|View full text |Cite
|
Sign up to set email alerts
|

Remote Control of Multimodal Nanoscale Ligand Oscillations Regulates Stem Cell Adhesion and Differentiation

Abstract: Cellular adhesion is regulated by the dynamic ligation process of surface receptors, such as integrin, to adhesive motifs, such as Arg-Gly-Asp (RGD). Remote control of adhesive ligand presentation using external stimuli is an appealing strategy for the temporal regulation of cell-implant interactions in vivo and was recently demonstrated using photochemical reaction. However, the limited tissue penetration of light potentially hampers the widespread applications of this method in vivo. Here, we present a strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 58 publications
(105 reference statements)
0
69
0
1
Order By: Relevance
“…For example, Du and others showed magnetic field‐mediated aggregation and stretching of stem cells with magnetic nanoparticles to induce their cardiac differentiation in vitro . Our own studies have shown that the magnetic field tuned the tether compliance or oscillation of ligand with magnetic nanoparticles to modulate stem cell differentiation into osteoblasts in vitro. Alternatively, among light stimuli in various wavelength, NIR light that can activate nanomaterials offers benefits of reduced phototoxicity and deep tissue penetration.…”
Section: Introductionmentioning
confidence: 89%
“…For example, Du and others showed magnetic field‐mediated aggregation and stretching of stem cells with magnetic nanoparticles to induce their cardiac differentiation in vitro . Our own studies have shown that the magnetic field tuned the tether compliance or oscillation of ligand with magnetic nanoparticles to modulate stem cell differentiation into osteoblasts in vitro. Alternatively, among light stimuli in various wavelength, NIR light that can activate nanomaterials offers benefits of reduced phototoxicity and deep tissue penetration.…”
Section: Introductionmentioning
confidence: 89%
“…Recent studies have used micro- and nanometer-scale engineered structures to mimic extracellular matrices and other biological structures, which have led to a groundbreaking understanding of the physical cues and molecular signal transduction pathways for integrin activated focal adhesion, protein adsorption, and pseudopodia formation [1,2,3,4,5,6,7,8,9]. Results have shown that cellular responses often depend on the mechanical properties, pattern structures, and surface chemistry of the microenvironment surrounding the cells [1,3,4,5,7,8,10,11,12,13,14,15,16,17,18,19,20]; however, work done thus far has been conducted with structures composed of monolithic materials having uniform surface chemical composition.…”
Section: Introductionmentioning
confidence: 99%
“…Besides ion channels, mechanosensitive receptors such as integrins and the Wnt receptor Frizzled have been targeted and magnetically activated to directly regulate cell proliferation and differentiation . Recently, Bian and co‐workers reported both in vitro and in vivo regulation of stem cell adhesion and differentiation using integrin ανβ 3‐targeting MIONs tethered with the RGD peptide under a low AMF (0.1 Hz). Rotherham et al designed MIONs functionalized with an anti‐Frizzled protein which were able to activate Wnt signaling in MSCs under an external magnetic field.…”
Section: Mions In Regenerative Medicine Applicationsmentioning
confidence: 99%